Trust Management IX 9th IFIP WG 11.11 International Conference, IFIPTM 2015, Hamburg, Germany, May 26-28, 2015, Proceedings - Damsgaard Jensen, Christian; Marsh, Stephen; Dimitrakos, Theo.; Murayama, Yuko.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 9th IFIP WG 11.11 International Conference on Trust Management, IFIPTM 2015, held in Hamburg, Germany, in May 2015. The 10 revised full papers and 5 short papers presented were carefully reviewed and selected from 28 submissions. In addition, the book contains one invited paper and 5 papers from a special session on trusted cloud ecosystems. The papers cover a wide range of topics including trust and reputation and models thereof, the relationship between trust and security, socio-technical aspects of trust, reputation and privacy, trust in the cloud and behavioural models of trust.
Reputation - from Social Perception to Internet Security -- Mathematical Modelling of Trust Issues in Federated Identity Management -- Simple and Practical Integrity Models for Binaries and Files -- Enabling NAME-Based Security and Trust -- Trust Driven Strategies for Privacy by Design -- Lightweight Practical Private One-Way Anonymous Messaging -- Privacy-Preserving Reputation Mechanism: A Usable Solution Handling Negative Ratings -- Obscuring Provenance Confidential Information via Graph Transformation -- Social Network Culture Needs the Lens of Critical Trust Research -- Predicting Quality of Crowd sourced Annotations Using Graph Kernels -- An Architecture for Trustworthy Open Data Services -- 1,2, Pause: Lets Start by Meaningfully Navigating the Current Online Authentication Solutions Space -- Data Confidentiality in Cloud Storage Protocol Based on Secret Sharing Scheme: A Brute Force Attack Evaluation -- The Detail of Trusted Messages: Retweets in a Context of Health and Fitness -- Reusable Defense Components for Online Reputation Systems -- Continuous Context-Aware Device Comfort Evaluation Method -- Special Session: Toward Trusted Cloud Ecosystems -- Foreword: Towards Trusted Cloud Ecosystems -- A Cloud Orchestrator for Deploying Public Services on the Cloud – The Case of STRATEGIC Project -- Integrating Security Services in Cloud Service Stores -- Building an Eco-System of Trusted Services via User Control and Transparency on Personal Data -- Security-as-a-Service in Multi-cloud and Federated Cloud Environments -- The Role of SLAs in Building a Trusted Cloud for Europe.
Keywords: Computers and civilization; Computer security; Computers; Computers and Society; Systems and Data Security; Information Systems and Communication Service